2015
DOI: 10.18632/oncotarget.6049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel Nodal-targeting monoclonal antibody in melanoma

Abstract: Nodal is highly expressed in various human malignancies, thus supporting the rationale for exploring Nodal as a therapeutic target. Here, we describe the effects of a novel monoclonal antibody (mAb), 3D1, raised against human Nodal. In vitro treatment of C8161 human melanoma cells with 3D1 mAb shows reductions in anchorage-independent growth and vasculogenic network formation. 3D1 treated cells also show decreases of Nodal and downstream signaling molecules, P-Smad2 and P-ERK and of P-H3 and CyclinB1, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 54 publications
(68 reference statements)
0
30
0
Order By: Relevance
“…Nodal was found to be associated with advanced stages of melanoma, breast, prostate, pancreatic, ovarian and colon cancer, in addition to glioblastoma and neuroblastoma (25). Collectively, these results supported the potential of Nodal as a valuable prognostic biomarker and promising new target to inhibit tumorigenicity and metastasis (26).…”
Section: Melanoma Embryonic Phenotypementioning
confidence: 54%
See 1 more Smart Citation
“…Nodal was found to be associated with advanced stages of melanoma, breast, prostate, pancreatic, ovarian and colon cancer, in addition to glioblastoma and neuroblastoma (25). Collectively, these results supported the potential of Nodal as a valuable prognostic biomarker and promising new target to inhibit tumorigenicity and metastasis (26).…”
Section: Melanoma Embryonic Phenotypementioning
confidence: 54%
“…To pursue this concept, we tested the effects of anti-Nodal antibody therapy on melanoma mouse models injected with metastatic tumor cells. The results showed a reduction in tumor growth at the primary site of orthotopic injection, and a reduction in lung tumor burden in the experimental metastasis model (25,27,28). Although these studies were promising, this approach using monotherapy to target only Nodal-expressing melanoma cells did not completely inhibit tumor formation.…”
Section: Melanoma Embryonic Phenotypementioning
confidence: 99%
“…Previous studies using anti-Nodal neutralizing antibodies have demonstrated changes to signaling pathways and molecular markers including reduced phosphorylation of histone 3 at serine 10 (pH3 Ser10 ), and a reduction in the proform of Nodal in cell lysates, which may be a result of inhibition of Nodal auto-regulatory mechanisms. 13,16,31 In doxorubicin treated cells, treatment with anti-Nodal antibody led to decreases in both Nodal protein levels and pH3…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent findings that have reported the embryonic morphogen Nodal as a driver of cancer cell growth, plasticity, and highly expressed in aggressive cancers, are complemented by experimental studies showing Nodal inhibition resulting in suppression of tumorigenesis and the cancer stem cell phenotype. 13,17,31 In this study, we analyzed Nodal expression in a group of invasive breast cancer samples and found Nodal to be more highly expressed in TNBC when compared to invasive HR and HER2 positive breast cancers. These data advance a previous study in which Nodal expression was found to be significantly higher in TNBC compared to benign breast tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation